2017
DOI: 10.4314/sajas.v47i5.4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of β-galacto-oligosaccharide on growth performance and components of intestinal barrier in broilers during heat stress

Abstract: This study aimed to investigate the influence of β-galacto-oligosaccharides (β-GOS) on growth performance, organ development and intestinal microarchitecture of broilers during heat stress. Day-old chicks (n = 125) were divided into five groups. The control or thermoneutral zone group (TNZ) was raised under standard management until the 35th day. Four groups were exposed to cyclic heat stress (35 °C 8 h/d) from the 22nd to the 35th day. The TNZ and heat stress control (HSCT) groups were fed a corn-based diet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…In this study, HS is seen to reduce duodenal villus width, as well as villus height and width in the jejunum. These morphometric and histopathological changes, possibly resulting from ischemia and hypoxia accompanied by epithelial shedding are consistent with other reports in heat-stressed birds ( Deng et al, 2012 ; Ashraf et al, 2017 ; Li et al, 2020 ). Conversely, Quinteiro-Filho et al (2010) reported that HS (31 ± 1 and 36 ± 1°C/10 h/d) evoked no significant changes in villus and crypt morphology in broiler chickens.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, HS is seen to reduce duodenal villus width, as well as villus height and width in the jejunum. These morphometric and histopathological changes, possibly resulting from ischemia and hypoxia accompanied by epithelial shedding are consistent with other reports in heat-stressed birds ( Deng et al, 2012 ; Ashraf et al, 2017 ; Li et al, 2020 ). Conversely, Quinteiro-Filho et al (2010) reported that HS (31 ± 1 and 36 ± 1°C/10 h/d) evoked no significant changes in villus and crypt morphology in broiler chickens.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the dietary enzyme supplementation of poultry diets did not have any beneficial effects on feed efficiency. Present FCR values were similar with values reported by Al-Hsawi [58] and Shahbazi [60], but were not similar to those reported by Ehsani and Torki [5] or Ashraf et al [61].…”
Section: Feed Intake and Feed Conversion Ratiosupporting
confidence: 80%
“…However, Liu et al [11] suggested short-term intake of high-dose GOS and FOS prebiotics had an adverse effect on glucose metabolism despite increased Bifidobacterium in the fecal microbiota. In controlled animal studies, GOS has been associated with improved growth performance of broiler chickens [12] or during exposure to heat stress [13,14]. Dietary supplementation of GOS has also been linked with improvements in the transition to a mature intestinal microbiota in broiler chickens [12,15] and in suckling piglets [16,17].…”
Section: Introductionmentioning
confidence: 99%